ChemInform Abstract: Interfacial Hydrogenation and Deamination of Nitriles to Selectively Synthesize Tertiary Amines. Issue 8 (February 2015) - Lu, Shuanglong; Li, Chao; Wang, Jiaqing; Pan, Yue; Cao, Xueqing; Gu, Hongwei
Abstract Tertiary amines are successfully synthesized from the interfacial hydrogenation of nitriles in one pot using highly active and stable Pt nanowires as the catalyst.